Prevalence of metabolic syndrome in Psoriasis – a case control study - K.V.T. Gopal; G. Deepika Raj; T. Narayana Rao (International Journal of Medical Research and Review, 2015)
Introduction: Recently, associations between psoriasis and metabolic disorders such as obesity, diabetes, and atherogenic dyslipidemia have been recognized. The present study was performed to know the prevalence of metabolic syndrome and its individual components in Psoriatic patients and compare them with age and sex matched controls.Methods: The study included 60 psoriatic patients and 60 age and sex matched controls. Severity of psoriasis was assessed according to psoriasis area and severity index (PASI) score. Waist circumference, blood pressure, fasting plasma glucose, serum cholesterol, HDL, LDL, VLDL and triglycerides were recodrded in all patients and controls. Metabolic syndrome was diagnosed by the presence of three or more of the five criteria of the 2005 revised National Cholesterol Education Programme’s Adult Treatment Panel III . Statistical analysis of the data was performed.Results: Prevalence of metabolic syndrome was seen in 20 cases (33.3%) compared to 9 (15%) controls which was statistically significant (P = 0.019). Metabolic syndrome, high fasting blood glucose, high triglyceride levels and low HDL levels were significantly more in cases than controls. There was no significant difference in the prevalence of abdominal obesity and hypertension among cases and controls.Conclusion: There is a need for regular evaluation of psoriatic patients, even younger patients and those with mild disease, for the presence of any of the components of metabolic syndrome. Dermatologists should screen all psoriasis patients to detect the existence of comorbid conditions such as metabolic syndrome and its individual components.